Multiple Targeted Therapy is Critical for Reducing Cardiometabolic Risk - Koh, Kwang Kon (MD Conference Express, 2011)
Obesity is associated with a range of adverse metabolic consequences, including endothelial dysfunction, systemic inflammation, and insulin resistance. Therefore, to provide effective protection against the development of atherosclerosis and heart disease, obese patients require combination drug regimens that target several cardiometabolic risk factors.